97.0k views
4 votes
Would you need to use the chain rule to find the derivative of this function?

Would you need to use the chain rule to find the derivative of this function?-example-1
User AlexH
by
5.2k points

1 Answer

6 votes

Answer:

TRUE. We need to use the chain rule to find the derivative of the given function.

Explanation:

Chain rule to find the derivative,

We have to find the derivative of F(x)

If F(x) = f[g(x)]

Then F'(x) = f'[g(x)].g'(x)

Given function is,

y =
√(2x+3)

Here g(x) = (2x + 3)

and f[g(x)] =
√(2x+3)


(dy)/(dx)=(d)/(dx)(√(2x+3)).(d)/(dx) (2x+3)

y' =
(1)/(2)(2x+3)^{(1-(1)/(2))}.(2)

=
(2x+3)^{-(1)/(2)}

y' =
(1)/(√(2x+3))

Therefore, it's true that we need to use the chain rule to find the derivative of the given function.

User Wallice
by
5.6k points